The Gender Pay Gap in Austria: Tamensi Movetur! - René Böheim; Klemens Himpele; Helmut Mahringer; Christine Zulehner (Austrian Institute of Economic Research (WIFO), 2011)
Policies to reduce the gender pay gap feature prominently on the political agenda and interventions in the labour market are frequently proposed, claiming a persistent wage gap. We examine the change of the gender wage gap in Austria between 2002 and 2007 with new data from administrative records and find that it declined from 24 percent in 2002 to 19 percent in 2007. We observe that women's improved educational attainments were partly offset by a shift in the demand for skilled workers that disadvantaged unskilled labour. The main determinant of this decline is however the improvement of women's relative position in unobserved characteristics.
Keywords: 330; gender wage differentials; wage inequality; decomposition; matched employer-employee data; Lohnstruktur; Geschlecht; Dekompositionsverfahren; Österreich